Do geographic location and historical conditions affect the quality and availability of open cadastral data? From early cadastral maps till now - Busko Małgorzata; Balawejder Monika; Kovalyshyn Oleksandra; Apollo Michal (Reports on Geodesy and Geoinformatics, 2023)
Since the early days, cadastral data represent the geographic extent of the past, current, and future rights and interests in real property. Thus, these data are extremely important for the proper development of statehood and society. The article analyses the process of formation of the real estate cadastre in two countries – Poland and Ukraine – from the time of its establishment to the present. Both countries were in the past (and Ukraine still is) victims of various historical events that deprived them of statehood, stability and opportunities for development; therefore, it affected the development of the cadastre and its accessibility to all stakeholders. The authors attempt to answer the question of if and how geographic location and historical conditions can affect the quality and availability of open cadastral data (OCD). After all, our perception of reality is a direct result of processes originating in history. This paper contains comparisons between a post-Soviet (Ukraine) and a post-communist country (Poland) and their path from early cadastral maps to OCD.